Molecular conformation of then published Ziziphus budhensis and its religious and economic values - Pathak, M. L.; Li, H. C.; Xu, B.; Gao, X. F.; Pokharel, K. K.; Nagarkoti, A. B. (Banko Janakari, 2017)
The newly described species, Ziziphus budhensis was confirmed as Chinese Jujuba, Z. xiangchengensis on the basis of their DNA analyses. Z. budhensis was explained as a new species on the basis of some morphological differences in 2015. In the Year 2016, the DNA samples were collected from the type locality of Nepal, and the molecular analyses were carried out. The type specimens and the other available images from the different herbariums were examined. Besides, the protologue and the type images were studied carefully. The result showed that though there were some differences in the habit and the habitat of the plant, the previously described new species, Z. budhensis was found to be same as the Chinese species, Z. xiangchengensis. This study also showed the importance of the molecular work of Z. budhensis and confirmed it morphologically distinct although it was very close to the Chinese species. Banko Janakari, Vol. 27, No. 1, page: 55-59